Treatment of non-epileptic episodes of anxious, fearful behavior in adolescent juvenile neuronal ceroid lipofuscinosis (CLN3 disease) - Ostergaard, John R. (Frontiers in Neurology, 2023)
Background Recurrent non-epileptic episodes of frightened facial and body expression occur in more than half of post-adolescent patients with juvenile neuronal ceroid lipofuscinosis (JNCL, CLN3 disease). Clinically, the episodes look similar to the attacks of paroxysmal sympathetic hyperactivity (PSH) commonly seen following traumatic brain injury (TBI). The episodes occur when the patients are exposed to separation, hear loud sounds or are otherwise bothered by discomfort and as in PSH following TBI, the attacks are difficult to prevent and/or treat. Aim and methods Based on present knowledge of triggering factors, the neural anxiety/fear circuit, its afferent and efferent pathways and documented CLN3 disease-impact on these tracks, the current study discusses a rational approach how to prevent and/or treat the attacks. Results Patients with JNCL have a disturbed somatosensory modulation leading to a reduced threshold of pain; a degeneration within the neural anxiety/fear circuit leading to an imbalance of central network inhibition and excitation pathways; and finally, an, with advancing age, increasing autonomic imbalance leading to a significant dominance of the sympathetic neural system. Discussion Theoretically, there are three points of attack how to prevent or treat the episodes: (1) increase in threshold of discomfort impact; (2) modulation of imbalance of central network inhibition and excitation, and (3) restoring the balance between the sympathetic and parasympathetic neural systems prompted by a parasympathetic withdrawal. As to (1) and (2), prevention should have the greatest priority. As regards (3), research of transcutaneous vagal stimulation treatment in JNCL is warranted.